1981
DOI: 10.1523/jneurosci.01-11-01236.1981
|View full text |Cite
|
Sign up to set email alerts
|

Axonal ramifications of hippocampal Ca1 pyramidal cells

Abstract: Intracellular injections of Lucifer Yellow into CA1 pyramidal cells of the in vitro guinea pig hippocampal slice enabled us to examine in detail the morphology of the axons of these neurons. We also recorded the electrophysiological responses of these neurons to alvear stimulation. In our morphological examinations, we found that many axons bifurcate in the alveus, with the major branch projecting caudally toward the subiculum and the second, thinner branch projecting rostrally toward the fimbria. Either axons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…Two-photon imaging of intracellularly labeled CA1 pyramidal neurons shows that every CA1 pyramidal neuron that was examined sends out a longitudinally oriented axon that branches off, and is perpendicular to, the thick, well-established projection that goes toward the subiculum and fimbria. The subicular and fimbrial axonal projections agree with established data (17), but the longitudinally projecting collateral has not been described. Note that although we use the term "longitudinal" as others have, that this term was done partly for convenience: The most favorable orientation for excitatory effects was in the longitudinal plane; however, stimulation at angles oblique to the longitudinal plane was also quite effective in activating CA1 pyramidal cells.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Two-photon imaging of intracellularly labeled CA1 pyramidal neurons shows that every CA1 pyramidal neuron that was examined sends out a longitudinally oriented axon that branches off, and is perpendicular to, the thick, well-established projection that goes toward the subiculum and fimbria. The subicular and fimbrial axonal projections agree with established data (17), but the longitudinally projecting collateral has not been described. Note that although we use the term "longitudinal" as others have, that this term was done partly for convenience: The most favorable orientation for excitatory effects was in the longitudinal plane; however, stimulation at angles oblique to the longitudinal plane was also quite effective in activating CA1 pyramidal cells.…”
Section: Discussionsupporting
confidence: 72%
“…It has been proposed that the previously described sparse associational projections to neighboring transverse lamellae in CA1 are primarily directed onto inhibitory interneurons (17,18). To investigate whether the associational axonal processes described here represent excitatory-excitatory or excitatory-inhibitory connections, we looked for immunohistochemical evidence of contact with synaptic spines of pyramidal neurons.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, MacVicar & Dudek (1981) reported that the small fast prepotentials detected at the somata of CA3 pyramidal cells are a reflexion of electrical coupling rather than of dendritic spikes. Knowles & Schwartzkroin (1981) recently suggested that the fast prepotentials are a passive reflection of action potentials in axonal collaterals of the pyramidal cells. Jeffereys (1979) found that in dentate granular cells, the action potential is generated in the soma and is only triggered by the dendritic e.p.s.p.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical evidence for a dense projection from CA1 to subiculum is well established (Witter and Amaral, 2004). There are examples of individual CA1 neurons with pronounced asymmetries of their axonal arbors (Finch and Babb, 1981;Knowles and Schwartzkroin, 1981;Tamamaki et al, 1987), although some cells have symmetrical axonal arbors (Finch et al, 1983). Importantly, for the development of the argument that projection collaterals contribute to the asymmetry of the intrinsic collateral system, there are several examples of CA1 pyramidal cells showing axonal extensions that reach up into stratum oriens arising from the major collaterals (Knowles and Schwartzkroin, 1981;Lorente de No, 1934).…”
Section: Bases For the Asymmetry In Ca1mentioning
confidence: 99%
“…There are examples of individual CA1 neurons with pronounced asymmetries of their axonal arbors (Finch and Babb, 1981;Knowles and Schwartzkroin, 1981;Tamamaki et al, 1987), although some cells have symmetrical axonal arbors (Finch et al, 1983). Importantly, for the development of the argument that projection collaterals contribute to the asymmetry of the intrinsic collateral system, there are several examples of CA1 pyramidal cells showing axonal extensions that reach up into stratum oriens arising from the major collaterals (Knowles and Schwartzkroin, 1981;Lorente de No, 1934). Lorente de Nó described both the local axonal arbors around individual CA1 cells (Lorente de No, 1934) (we have similar data from Golgi studies in rats, unpublished), and collaterals arising from CA1 alvear fibers that entered the ''lower parts'' of CA1.…”
Section: Bases For the Asymmetry In Ca1mentioning
confidence: 99%